ANALISYS TO COMPUTER-RELATED FRAUD - Ávila Trivelli, Anderson Abraham (2023)
The present research work contemplates an analysis of the criminal type of Computer Fraud in Peruvian legislation, also analyzing the classification established in the Convention on Cybercrime or Budapest Convention, also making reference to the Argentine and Spanish legislation for which the qualitative method, oriented to the analysis of the criminal types of the aforementioned regulations, obtaining as a result that our regulations are in strict accordance with what is determined in the international standard; being a classification identical to that established in the Budapest Convention. Thus, it can also be concluded that the criminal type of computer fraud turns out to be broader in our legislation than in Argentine and Spanish legislation, finding ourselves faced with a multi-offensive crime, highlighting the atypicality in mediating consent on the part of the passive subject in the execution of the conduct of the criminal offense carried out by the active subject.